1994
DOI: 10.1104/pp.104.2.535
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Expression Pattern of Sucrose Synthase during Tomato Fruit Development

Abstract: Sucrose synthase is proposed to play an important role in the early stages of tomato fruit (Lycopersicon esculentum Mill.) growth. In this work, the temporal and spatial expression patterns of sucrose synthase during tomato fruit development were investigated. Fruit contained the majority of the sucrose synthase protein and mRNA relative to other organs. Only trace levels of sucrose synthase protein and mRNA were detected in the stem, petiole, and roots. Sucrose synthase mRNA was detected in pistils prior to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 24 publications
8
33
1
Order By: Relevance
“…The major form of sucrose synthase mRNA in young tomato fruits comes from the sus2 gene and increased dramatically from DAP 5 to DAP 20 in fruits of S. lycopersicum and similarly in S. peruvianum. In contrast to our Wndings, Wang et al (1994) reported that sucrose synthase mRNA reached peak levels in fruits 5-7 days after anthesis. In that case, though, no distinction was made between sus3 and sus2 mRNA, but at that stage in development, sus2 is more highly expressed than sus3.…”
Section: Regulation Of Gene Expressioncontrasting
confidence: 99%
“…The major form of sucrose synthase mRNA in young tomato fruits comes from the sus2 gene and increased dramatically from DAP 5 to DAP 20 in fruits of S. lycopersicum and similarly in S. peruvianum. In contrast to our Wndings, Wang et al (1994) reported that sucrose synthase mRNA reached peak levels in fruits 5-7 days after anthesis. In that case, though, no distinction was made between sus3 and sus2 mRNA, but at that stage in development, sus2 is more highly expressed than sus3.…”
Section: Regulation Of Gene Expressioncontrasting
confidence: 99%
“…In addition, the spatial expression of Sue synthase mRNA correlates with starch granule accumulation (Wang et al, 1994). The Frk2 mRNA is also expressed at high levels during this same developmental stage.…”
Section: Discussionmentioning
confidence: 86%
“…In tomato (Lycopersicon esculentum) starch accumulates during the early stage of fruit development and then decreases during maturation (Yelle et al, 1988). SUC synthase has been proposed to be the primary enzyme in the metabolism of imported Suc during the early developmental stages, and localization of its mRNA suggests a relationship between SUC synthase and starch granule accumulation (Wang et al, 1993(Wang et al, , 1994. In addition, invertase has been identified in the intercellular fraction, and it is suggested that hexose produced by invertase is actively imported across the plasma membrane (Sato et al, 1993;Ruan and Patrick, 1995).…”
Section: ~ ~ ~mentioning
confidence: 99%
“…It is not known, however, whether the different tissues of tomato fruit have different sink status at early stages of development. Wang et al (1994) have analyzed the pattern of SUC synthase mRNA distribution in developing tomato fruit as a marker for sink tissue activity. Interestingly, the highest leve1 of Suc synthase mRNA and the highest concentration of starch were found in the pericarp and columnella tissues.…”
Section: Cellular Sink Activity and Rbcs Promoter Activity Are Exclusivementioning
confidence: 99%